THE STRATEGY TO IMPROVE CLEAN WATER SERVICES IN BENGKULU PROVINCE - Siti Yuningsih; Kamaludin; Muhartini Salim; Rina Suthia Hayu (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Based on the conditions of the three PDAM offices in Bengkulu Province, it shows that the availability of clean water in Bengkulu Province is as follows: 1) the quality of clean water is still low and the suitability of clean water sources does not meet quality standards; 2) the needs of water are increasing (quantity); 3) the need for clean water continues to increase over time (continuity); 4) clean water management is not optimal (affordability) based on the Performance Evaluation by BPKP on PDAM Bengkulu Province in 2019. This type of research is a descriptive with qualitative approach and this research is located in three location namely Central Bengkulu Regency, North Bengkulu Regency and Bengkulu City. The number of specimens in this research was 400 PDAM consumers. Based on the results of the SWOT analysis of improving service quality, it was found that EFAS and IFAS were in quadrant II (0.126; -0.245) with a diversification strategy. This result focuses on the 4 Ks (quantity, quality, continuity and affordability) according to J. Nijman (1997) and Barata (2003). Therefore, the regional drinking water company owned by the regional government of Bengkulu Province has improved the quality of clean water services which will have an impact on community welfare and independence in receiving public services in the clean water sector. The strategy to improve clean water services in Bengkulu province requires management based on customer satisfaction, clean water availability, quality, quantity and continuity based on regulations and business plans of companies that manage clean water owned by each PDAM office. Clean water services and management will also provide basic services for community needs, increasing profits, and retribution to regional income (PAD).